2018
DOI: 10.2106/jbjs.rvw.17.00138
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Outcomes After Medial Ulnar Collateral Ligament Reconstruction

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…The first model compared the effect of graft technique (docking vs figure-of-8 technique) across all studies (Figure 4A). Consistent with the findings of previous literature, 42,46,48 this model demonstrated a significantly higher proportion of excellent outcomes with docking reconstructions (86.58%; 95% CI, 80.42%-91.85%) than with figure-of-8 reconstructions (76.76%; 95% CI, 69.65%-83.25%; P = .031; I 2 = 87.07%). The second model examined the effect of graft technique across studies in which FPM-preserving approaches were used and no routine submuscular ulnar nerve transpositions were performed (Figure 4B).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The first model compared the effect of graft technique (docking vs figure-of-8 technique) across all studies (Figure 4A). Consistent with the findings of previous literature, 42,46,48 this model demonstrated a significantly higher proportion of excellent outcomes with docking reconstructions (86.58%; 95% CI, 80.42%-91.85%) than with figure-of-8 reconstructions (76.76%; 95% CI, 69.65%-83.25%; P = .031; I 2 = 87.07%). The second model examined the effect of graft technique across studies in which FPM-preserving approaches were used and no routine submuscular ulnar nerve transpositions were performed (Figure 4B).…”
Section: Resultssupporting
confidence: 90%
“…Multiple systematic reviews have suggested improved outcomes after UCL reconstruction with the docking technique as compared with the figure-of-8 technique. 22,42,46,48 Recent findings of several comparative cohort and large database studies have suggested that the differences in outcomes are not statistically significant. 2,25,32 Likewise, our findings revealed no significant difference in the proportions of excellent outcomes between UCL reconstruction performed with docking and figure-of-8 techniques when the FPM is preserved and routine submuscular ulnar nerve transposition is abandoned, as well as no significant difference in the mean time to RTP between techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-demand baseball pitchers are particularly prone to UCL injury and make up a large portion of patients undergoing UCL reconstruction. 15 In a survey of >5000 professional baseball players, 10% were found to have undergone at least 1 UCL reconstruction. Of the Major League Baseball (MLB) pitchers included in the survey, 25% reported that they had undergone the procedure.…”
mentioning
confidence: 99%